Descriptive Study of The Application of The Mind Mapping Method in Learning Islamic Civilization History Courses - Arditya Prayogi; Riki Nasrullah; Novianto Ade Wahyudi (Yayasan Cendekiawan Indonesia Timur, 2025)
This study addresses the monotonous use of lecture-based methods in teaching the History of Islamic Civilization (SPI) at the Faculty of Tarbiyah and Teacher Training, UIN KH Abdurrahman Wahid Pekalongan. It aims to examine the implementation of the mind mapping method as an innovative alternative to enhance student engagement and comprehension. Employing a qualitative descriptive approach within a case study design, data were collected through interviews, observations, and documentation. The findings reveal that the integration of the mind mapping method in SPI learning occurs through several key stages: establishing learning contracts, deepening conceptual understanding, creating and presenting mind maps, delivering material using mind mapping, and conducting interactive discussions. The study identifies both supporting and inhibiting factors influencing the implementation process. Supporting factors include students’ enthusiasm, collaborative learning, and the flexibility of online learning platforms, while inhibiting factors relate to limited digital skills and time constraints. Overall, the application of the mind mapping method fosters creativity, strengthens analytical thinking, enhances comprehension of historical materials, and provides a reference for developing more interactive learning models. The findings imply that adopting mind mapping in higher education, particularly in historical studies, can transform traditional pedagogical practices into more participatory and student-centered learning experiences.